ANALISIS KUALITAS AIR DAN LINGKUNGAN FISIK PADA PERLINDUNGAN MATA AIR DI KERJA PUSKESMAS TABANAN I, KABUPATEN TABANAN - ARYANA, I KETUT; Mahendra, Made Sudiana; Mahardika, I Gede (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 5 No 2, 2010)
1his research was intended to find out water quality and physical environmental condition in the springs protection in the working area of public health center Tabanan I, regency of Tabanan. 1his assessment was performed by physical, chemical and bacteriological analysis, as well as index of water pollution and physical environmental condition, vegetation and public activity in the environment of water springs protection. 1his research was descriptive qualitative using the method of quantitative approach. The sample was 15 (fifteen) units in February and 15 (fifteen) units in May 2010. The unit was obtained by doing the method of purposive sampling for the water sample. Sample type was a grab sample. The water quality, if compared to the standard of the First quality water Ordinance of Bali Governor No. 8. Year 2007, and the ordinance of the minister of Health republic of Indonesia No. 907 Year 2002, regarding the requirement of the supervision of the quality of drinking water, index of pollution according to the provision of the minister of environment No. 115 Year 2003 as well as physical condition refer to the program of surveillance of quality of clean water general director of the eradication of contagious disease and betterment of living spaces, through sanitation inspection of water source protection. Result of the research showed that there were 1 (one) parameters, they were BOD 5 in February and May 2010 over water standard of first quality water ordinance of Bali governor No. 8 Year 2007. Pollution index showed that in February 2010, there was one springs protection with the value of 0 ?  IP ?  1 with the status of good condition but the other value was 1 ? IP ?  5 including light pollution. In May 2010, all included slight pollution with the value of 1 ?  IP ?  5.
Keywords: water quality, water springs protection, physical environmental